A Sub-μA Ultrasonic Wake-Up Trigger with Addressing Capability for Wireless Sensor Nodes. (19th September 2013) - Lattanzi, Emanuele; Dromedari, Matteo; Freschi, Valerio; Bogliolo, Alessandro
Abstract : Wireless sensor nodes spend most of the time waiting either for sensed data or for packets to be routed to the sink. While on board, sensors can raise hardware interrupts to trigger the wake-up of the processor, incoming packets require the radio module to be turned on in order to be properly received and processed; thus, reducing the effectiveness of dynamic power management and exposing the node to unintended packets cause energy waste. The capability of triggering the wake-up of a node over the air would makes it possible to keep the entire network asleep and to wake up the nodes along a path to the sink whenever there is a packet to transmit. This paper presents an ultrasonic wake-up trigger for ultra-low-power wireless sensor nodes developed as a plug-in module for VirtualSense motes. The module supports a simple out-of-band addressing scheme to enable the selective wake-up of a target node. In addition, it makes it possible to exploit the propagation speed of ultrasonic signals to perform distance measurements. The paper outlines the design choices, reports the results of extensive measurements, and discusses the additional degrees of freedom introduced by ultrasonic triggering in the power-state diagram of VirtualSense.